Interface engineering on phenanthrocarbazole/thienopyrroledione-based conjugated polymer for efficient organic photovoltaic devices with ideal nano-morphology and improved charge carrier dynamics. (October 2017) - Jang, Woongsik; Cheon, Hyungin; Park, Soyun; Cho, Jae Sang; Yi, Minji; Kwon, Soon-Ki; Kim, Yun-Hi; Wang, Dong Hwan
Abstract: We synthesized PP-TPD, based on a phenanthro[1, 10, 9, 8-cdefg]carbazole unit as a donor and a thieno [3, 4-c]pyrrole-4, 6-dione (TPD) unit as an acceptor for efficient bulk heterojunction photovoltaic cells. The copolymer achieves a relatively low bandgap (1.6 eV) by its internal charge-transfer, which concurs with the results of density functional theory (DFT) calculation for the distribution of HOMO and LUMO levels. In addition, we fabricated the bulk-heterojunction (BHJ) photovoltaic cells as a function of the blend ratio of the donor (PP-TPD) and acceptor (PC70 BM), and applied a solvent additive and an interlayer to the device, with the optimized ratio used in this study. To comprehend the relationships between the device performance and the synergetic effects of 1, 8-diiodooctane (DIO) and titanium oxide (TiOx ) within the PP-TPD: PC70 BM blends, we investigated the hole mobility related to the charge carrier transport, the charge generation, and the charge transport resistance using space-charge limited current (SCLC) measurement, photocurrent analysis, and impedance spectroscopy, respectively. Especially, we implemented fluorescence imaging by Raman spectroscopy, which related to the charge generation and recombination dynamics within the surface of photoactive areas. Graphical abstract: Highlights: PP-TPD copolymer revealed well-distribution of HOMO/LUMO and band-gap of 1.6 eV. PP-TPD copolymer was designed to improve intermolecular interaction and carrier mobility. Interface engineering via additive and interlayer affects homogeneous thin film morphology. Enhanced electrical parameters of Voc, Jsc, and FF are analyzed by charge carrier dynamics. Fluorescence imaging was conducted for the study of charge generation and recombination.